PERAN DINAS SOSIAL KOTA BANDA ACEH DALAM PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KELUARGA HARAPAN (Studi Kasus: Kecamatan Ulee Kareng) - Nadila Shafira; Iqbal Ahmady; muliawati muliawati (Journal of Political Sphere, 2022)
Poverty is one of Indonesia's social problems. To overcome poverty, the government forms programs that are expected to reduce the poverty rate. Program Keluarga Harapan is one of the government's efforts to reduce poverty by meeting the health needs of education and family income for the poor and vulnerable poor. Dinas Sosial as an agency that plays a role in social problems has a role in the implementation of the Program Keluarga Harapan. This study aims to see how the role of the Dinas Sosial of Banda Aceh city in community empowerment through The Program Keluarga Harapan and how the impact of empowerment of the Program Keluarga Harapan on the recipient community of the Program Keluarga Harapan. This study used Bureaucratic Theory, the concept of the role of government, the concept of empowerment and the concept of poverty. This study used qualitative research methods with qualitative descriptive research. The Data obtained in the study through interviews and literature studies to obtain all secondary data consisting of reports and other important documents are processed qualitatively to produce an explanation. The results of this study is the Dinas Sosial of Banda Aceh City has a role as a facilitator, educator, community representatives and mediators and the impact of the Program Keluarga Harapan on the community is improving the family economy, improving health and children's development and improving family welfare. This research came to the conclusion that the Dinas Sosial of Banda Aceh city carried out its role very well in the community and in the implementation of the Program Keluarga Harapan.